THE CRIMINAL PROCEDURAL PHENOMENON OF THE OATH: A LEGAL RUDIMENT OR AN UNDERVALUED PUBLIC LAW PROCEDURE? - LATYPOV Vadim Sagit'yanovich (Правовое государство: теория и практика)
The author’s scientific focus is on the question of whether the oath, as a procedural mechanism, is an outdated legal rudiment that has irretrievably lost its relevance in the context of modern criminal justice, or whether the oath should be considered a valuable but underestimated public law procedure allowing to increase the efficiency of criminal proceedings by strengthening the moral responsibility of participants for the content (completeness and truthfulness) of testimony. Purpose: to analyse the procedural institution of the oath, to determine its potential for strengthening the trust of the population, participants in criminal proceedings towards the criminal justice system and increasing responsibility for giving evidence. In the course of the study, the method of historical analysis is used, which makes it possible to determine the role and significance of the oath in criminal proceedings in different periods; the comparative legal method based on the analysis of criminal procedure legislation of some foreign countries; as well as the method of legal modeling, which allows to determine what transformations are required in the existing regulatory basis of the swearing-in procedure for individual participants in Russian criminal proceedings. Results: the swearing-in procedure for participants in criminal proceedings contributes to the formation of a correct attitude of those questioned to their procedural obligation to give truthful and complete testimony, and increases public confidence in justice.